Correlation of Peer Assessment with Learning Achievement in Predict Observe Explain (POE) Learning - Widinda Normalia Arlianty (Universitas Islam Indonesia, 2018)
ABSTRACT: This study aims to determine the correlation between peer assessment with learning achievement. The learning achievement was obtained from the value of chemistry practicum by taking three values, namely the value of responses and the pretest values taken using written test, and the value of practical skills taken using the peer assessment observation sheet. This research is a descriptive study. The sample of this research is second-semester student, force 2015/2016 Chemical Education Study Program, Islamic University of Indonesia. Data analysis using nonparametric statistic correlation test Spearman Rank Order Correlation. Based on statistical analysis, it is found that there is a correlation between peer assessment and student learning achievement: 1) correlation of peer assessment with response 0,722; correlation of peer assessment with pretest of 0.651; and the correlation of peer assessment with practical skills of 0.617Keywords: peer assessment, learning achievement, correlationReceived: 15 January 2018, Revised: 15 February 2018, Accepted: 24 February